Analisis Beban Kerja Menggunakan NASA-TLX pada Operator Stasiun Kerja Bagian Produksi Pakaian Rajut - Bersa Kirandika; Nur Rahman As'ad (UNISBA Press, 2023)
ABSTRACK - Indah Fashion is a home industry that produces knitwear. Based on observations there are defective products in the knitting, linking, and steam processes due to operator negligence, so to repair defective products causes overtime hours that exceed the standard. Operator negligence and error are the effects of decreased performance due to increased boredom and decreased concentration caused by high workloads. Based on existing phenomena, measurement of the workload on 9 operators with details of 3 knitting operators, 3 linking operators, 2 overlock operator and 1 steam operator using The National Aeronautics and Space Administration Task Load Index (NASA-TLX) is needed, therefore this study aims to identify the workload perceived by those operators. The study was conducted on 9 operators in production departement. Based on the results of workload measurements, operators working on knitting, linking, and steam workstations are in